NILAI-NILAI SISTEM PEREKONOMIAN ISLAM DALAM RITUAL “MAPPADENDANG” - Abdul Rahim (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
One of Bugis Makassar culture or ritual routinely performed each year in agricultural activities (harvest) by all farmers is Mappadendang. This ritual is performed as a form of joy and gratitude to the Creator, for agricultural crops. Mappadendang also intended to preserve the cultural heritage of their ancestors. Mappadendang in Pinrang has the high philosophy and as a means of ancestor in strengthening the unity and integrity. The importance of cooperation in traditional ritual Mappadendang, including carrying values of the Islamic economic system, are serious work in finding halal sustenance, forming society with solid social order, fairness of income distribution which can remove the monopoly system, and the freedom of individual in social welfare.